Multidimensional phenotyping of the post‐COVID‐19 syndrome: A Swiss survey study. (16th August 2022) - Diem, Lara; Schwarzwald, Anina; Friedli, Christoph; Hammer, Helly; Gomes‐Fregolente, Livia; Warncke, Jan; Weber, Lea; Kamber, Nicole; Chan, Andrew; Bassetti, Claudio; Salmen, Anke; Hoepner, Robert
Abstract: Introduction: Post‐COVID‐19 syndrome affects approximately 10–25% of people after a COVID‐19 infection, irrespective of initial COVID‐19 severity. The aim of this project was to assess the clinical characteristics, course, and prognosis of post‐COVID‐19 syndrome using a systematic multidimensional approach. Patients and Methods: An online survey of people with suspected and confirmed COVID‐19 and post‐COVID‐19 syndrome, distributed via Swiss COVID‐19 support groups, social media, and our post‐COVID‐19 consultation, was performed. A total of 8 post‐infectious domains were assessed with 120 questions. Data were collected from October 15 to December 12, 2021, and 309 participants were included. Analysis of clinical phenomenology of post‐COVID‐19 syndrome was performed using comparative statistics. Results: The three most prevalent post‐COVID‐19 symptoms in our survey cohort were fatigue (288/309, 93.2%), pain including headache (218/309, 70.6%), and sleep–wake disturbances (mainly insomnia and excessive daytime sleepiness, 145/309, 46.9%). Post‐COVID‐19 syndrome had an impact on work ability, as more than half of the respondents (168/268, 62.7%) reported an inability to work, which lasted on average 26.6 weeks (95% CI 23.5–29.6, range 1–94, n = 168). Quality of life measured by WHO‐5 Well‐being Index was overall low in respondents with post‐COVID‐19 syndrome (mean, 95% CI 9.1 [8.5–9.8], range 1–25, n = 239). Conclusion: Fatigue, pain, and sleep–wake disturbances were the main symptoms of the post‐COVID‐19 syndrome in our cohort and had an impact on the quality of life and ability to work in a majority of patients. However, survey respondents reported a significant reduction in symptoms over 12 months. Post‐COVID‐19 syndrome remains a significant challenge. Further studies to characterize this syndrome and to explore therapeutic options are therefore urgently needed. Abstract : Fatigue, pain, and sleep–wake disturbances were the main symptoms of the post‐COVID‐19 syndrome in our cohort and had an impact on quality of life and ability to work in a majority of patients. However, survey respondents reported a significant reduction in symptoms over 12 months.